Providers or professionals: How our conceptions of physician as machine or person lead to burnout. (1st February 2021) - Liao, Lester
Abstract: Physician burnout is a major problem in medicine. Much literature focuses on personal and organizational factors and less on the cultural system underlying medicine. The term health care provider, as opposed to professional, is paradigmatic of how cultural influences have shaped the physician role. This term emphasizes provision that mirrors business and consumer transactions. The pressure to be a provider has been augmented by failures of the medical establishment, which creates a sense of distrust and the need for patients to be proactive in making demands of physicians. This is coupled with shifted expectations of the medical encounter created by technology and the pressure of a bureaucratic system that views physicians primarily as dispensers of services rather than as individual people. These factors create a milieu where physicians both act and feel like machines. While it is important to serve the public good, this idea has become warped and at the cost of physician health. Physicians should instead be understood primarily as professionals, which places the emphasis on the physician as an individual who professes an ethic of patient care that is internally motivated. The language physicians use to describe themselves must portray their humanity and their work in medicine.